Plasma nitriding device and plasma nitriding method
By using screens made of nickel or nickel-based alloys in low-temperature nitriding treatment, the problems of long low-temperature nitriding treatment and insufficient material corrosion resistance in the prior art are solved, and faster extended phase film formation and better mechanical and corrosion performance are achieved.
Patent Information
- Application Number
- JP2022138242
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-05-12
- Filing Date
- 2022-08-31
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2042-08-31
AI Technical Summary
In low temperature nitriding treatment, the prior art requires about 50 hours to form an extended phase film of the required thickness, and while increasing the nitriding rate, it may affect the corrosion resistance of the material.
Using a discharge nitriding device and method including near-steel and a screen made of nickel or nickel-based alloy, the diffusion rate of nitride is increased, thereby accelerating the formation of the extended phase film by adjusting the electrode configuration and using a nickel screen.
By using nickel screens, the diffusion rate of nitride is significantly improved, the time required to form an extended phase film is shortened, while the surface hardness and corrosion resistance of the material are improved.
Smart Images

Figure 0007665210000001 
Figure 0007665210000002 
Figure 0007665210000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a plasma nitriding apparatus and a plasma nitriding method for subjecting steel material to plasma nitriding treatment. [Background technology]
[0002] (Low temperature nitriding) Nitriding is an example of a surface modification treatment for steel materials (Patent Documents 1 and 2). Conventionally, nitriding is performed on austenitic stainless steel materials at temperatures of 723K (Kelvin) or higher. In this case, the surface hardness and wear resistance are improved by the precipitation of chromium (Cr) nitrides. However, the amount of Cr in solid solution in the stainless steel material decreases, which reduces the corrosion resistance.
[0003] In response to this, low-temperature nitriding, which performs nitriding at a lower temperature than conventionally, has been of interest in recent years. When low-temperature nitriding is performed on the stainless steel material, an extended phase in which nitrogen is dissolved in a supersaturated state is formed on the surface of the stainless steel material, improving the surface hardness, wear resistance, and fatigue resistance. Furthermore, at temperatures below 723K, the diffusivity of Cr dissolved in the stainless steel material is low, suppressing the nucleation of chromium nitrides, and thus preventing a decrease in corrosion resistance due to the precipitation of chromium nitrides. However, because this is a low-temperature treatment, a long treatment time is required to thicken the extended phase.
[0004] (Plasma nitridation) Generally, the types of nitriding treatment include a gas nitriding method using ammonia gas, a salt bath nitriding method using cyanide, and a plasma nitriding method using plasma formed by glow discharge in a low vacuum containing nitrogen gas. Of these, the plasma nitriding method is more suitable for nitriding stainless steel materials than other nitriding methods because it can reduce and remove oxides such as passive films on the surface of steel materials by mixing hydrogen gas and using collisions of hydrogen ions.
[0005] The plasma nitriding methods include DCPN (Direct Current Plasma Nitriding) treatment, in which the steel material is the cathode, ASPN (Active Screen Plasma Nitriding) treatment, in which a metal screen installed to surround the steel material is the cathode, and S-DCPN (Direct Current Plasma Nitriding using Screen) treatment, in which both the steel material and the screen are the cathode. Of these, the S-DCPN treatment improves the rate at which nitrogen diffuses into the steel material (nitriding rate) compared to the DCPN and ASPN treatments (Non-Patent Document 1). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2000-073156 A [Patent Document 2] JP 2011-042862 A [Non-patent literature]
[0007] [Non-Patent Document 1] A. Nishimoto, T. Fukube and T. Tanaka: Mater. Trans. 57 (2016) 1811-1815. [Non-Patent Document 2] S. Hamashima and A. Nishimoto: J. Japan Inst. Met. Mater. 85 (2021) 430-438. Summary of the Invention [Problem to be solved by the invention]
[0008] Even when the S-DCPN treatment is used, in the case of low-temperature nitriding, it takes about 50 hours for the film of the expansion phase to reach a desired thickness, and there is still room for improvement (Non-Patent Document 1).
[0009] An object of one aspect of the present invention is to provide a plasma nitriding apparatus and the like that can form an expansion phase film more quickly than conventional methods in a low-temperature nitriding process. [Means for solving the problem]
[0010] In order to solve the above problems, a plasma nitriding apparatus according to one embodiment of the present invention is a plasma nitriding apparatus that performs plasma nitriding treatment on a steel material, and includes a screen arranged in the vicinity of the steel material, and a DC power supply having a cathode electrically connected to the steel material and the screen, wherein the steel material is a stainless steel material, and the screen is formed from nickel or a nickel-based alloy.
[0011] Furthermore, a plasma nitriding method according to another aspect of the present invention is a plasma nitriding method for performing plasma nitriding treatment on a steel material, which includes a step of performing the plasma nitriding treatment using the steel material and a screen arranged in the vicinity of the steel material as cathodes, wherein the steel material is a stainless steel material and the screen is formed from nickel or a nickel-based alloy.
[0012] According to the above-mentioned configuration and method, the amount of nitrogen diffusion can be improved compared to the case where a conventional screen made of steel material is used, and as a result, the expansion phase film can be formed quickly.
[0013] In the plasma nitriding apparatus and the plasma nitriding method, the stainless steel material may be an austenitic, ferritic or two-phase stainless steel material. In this case, the amount of nitrogen diffusion can be reliably improved compared to the case where the conventional screen is used, and as a result, the extended phase film can be rapidly and reliably formed.
[0014] In the plasma nitriding apparatus and the plasma nitriding method, the stainless steel material may be an austenitic or duplex stainless steel material, in which case the austenitic expanded phase can be thickened more quickly than in the case of using the conventional screen, thereby improving pitting corrosion resistance. Effect of the Invention
[0015] According to one aspect of the present invention, an effect is achieved in that an expansion phase film can be formed more quickly than in the past in a low-temperature nitriding process. [Brief description of the drawings]
[0016] [Figure 1] 1 is a cross-sectional view showing an overview of a plasma nitriding apparatus according to an embodiment of the present invention. [Diagram 2] This is a table showing the chemical compositions of three stainless steel materials: SUS304, SUS430, and SUS329J4L. [Diagram 3] 1 is a graph showing the results of X-ray diffraction tests on the above three stainless steel materials that were subjected to an S-DCPN treatment. [Figure 4] FIG. 13 is a table showing the results of calculating the expansion rate of the lattice constant using the diffraction angles of the expansion phases of each of the three stainless steel materials obtained from the graph above. [Diagram 5] 1 is a graph showing the nitrogen element profiles obtained by glow discharge optical emission spectroscopy (GD-OES) for the three stainless steel materials treated with the S-DCPN method. [Figure 6] 3 is a photograph showing the results of observing the cross-sectional structure of the above-mentioned SUS304 steel material in Examples and Comparative Examples using an electron probe microanalyzer (EPMA). [Figure 7] 3 is a photograph showing the results of observing the cross-sectional structure of the above-mentioned SUS430 steel material in Examples and Comparative Examples using an EPMA. [Figure 8]3 is a photograph showing the results of observing the cross-sectional structure of the above-mentioned SUS329J4L steel material in Examples and Comparative Examples using an EPMA. [Figure 9] 1 is a graph showing the results of surface hardness tests on the three stainless steel materials treated with the S-DCPN method. [Figure 10] 4 is a photograph showing the results of observation of surface structure performed after the above-mentioned surface hardness test for the above-mentioned SUS329J4L steel material examples and comparative examples. [Figure 11] FIG. 2 is a table showing the results of elemental analysis of the surface structure. [Figure 12] 1 is a graph showing the results of a polarization test on the above three stainless steel materials that were subjected to the S-DCPN treatment. [Figure 13] 4 is a photograph showing the corroded surface after the polarization test. [Figure 14] 1 is a photograph showing the results of elemental analysis of a crevice corrosion portion of the above-mentioned SUS329J4L steel material. [Figure 15] 1 is a graph showing nickel element profiles obtained by GD-OES for the three stainless steel materials subjected to the S-DCPN treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Before describing one embodiment of the present invention, the low-temperature nitriding process and the plasma nitriding method will be described in detail.
[0018] (Low temperature nitriding) When austenitic stainless steel is subjected to low-temperature nitriding treatment at 723K or lower, the austenitic phase (γ phase) becomes an expanded austenite phase (S phase or γ phase) in which nitrogen is supersaturated in the austenitic phase (γ phase). N A chromium phase) is formed on the surface of the stainless steel material, improving the surface hardness, wear resistance, fatigue resistance and corrosion resistance. At temperatures of 723K or less, the diffusivity of chromium dissolved in the stainless steel material is low, and nucleation of chromium nitrides is suppressed, so that a decrease in corrosion resistance due to the precipitation of chromium nitrides can be prevented.
[0019] When ferritic stainless steel is subjected to low-temperature nitriding, the ferritic phase (α phase) is dissolved in a supersaturated state with nitrogen to form an extended ferritic phase (Sα phase or α N In addition, when a low-temperature nitriding treatment is performed on a two-phase stainless steel material, an S phase and an Sα phase are formed on the surface of the stainless steel material in the gamma and alpha phases that are mixed at a ratio of about 1:1, or nitrogen (a gamma stabilizing element) is diffused to transform the alpha phase into the S phase, and only the S phase is formed on the surface of the stainless steel material. As a result, the surface hardness, wear resistance, fatigue resistance, and corrosion resistance of the stainless steel material are improved.
[0020] Thus, in the case of the low-temperature nitriding treatment, the mechanical properties, corrosion resistance, etc. of stainless steel can be improved by forming the above-mentioned extended phases (expanded austenite phase and expanded ferrite phase). However, since the low-temperature nitriding treatment is a low-temperature treatment, a long treatment time is required to thicken the extended phase.
[0021] (Plasma nitridation) As described above, plasma nitridation methods include the DCPN process, the ASPN process, and the S-DCPN process.
[0022] In the DCPN process, a voltage is applied to the steel material as a cathode, whereby plasma is formed on the surface of the steel material, and excited nitrogen species are generated. At this time, a high cathode voltage is applied to the steel material, which may cause problems such as melting of the steel material due to abnormal discharge and non-uniform nitriding due to edge effects.
[0023] The ASPN process is also called a cathode cage plasma nitriding (CCPN) process. In the ASPN process, a steel material is insulated, and a voltage is applied to a metal screen that is installed so as to surround the steel material, using the screen as a cathode, to generate plasma on the surface of the screen. Metal atoms that are knocked out by sputtering of nitrogen ions on the screen combine with excited species of nitrogen in the plasma to form metal nitrides. The metal nitrides accumulate on the surface of the steel material and decompose, causing nitrogen to diffuse into the steel material, and the nitriding of the steel material progresses.
[0024] Therefore, in the case of the ASPN process, since a high voltage is not applied to the steel material, the above problems in the DCPN process do not occur. However, the layer (deposit layer) formed by the metal nitrides originating from the screen and deposited on the surface of the steel material becomes thicker with the passage of processing time, and inhibits the diffusion of nitrogen in the steel material. Therefore, the rate at which nitrogen diffuses into the treated member (nitriding rate) is slower in the ASPN process than in the DCPN process.
[0025] In the S-DCPN process, a voltage is applied to both the steel and the screen as cathodes, and the screen functions as a heater to reduce the cathode voltage applied to the steel. This makes it possible to suppress the edge effect that occurs in the DCPN process. Furthermore, the nitriding rate is improved compared to the DCPN process and the ASPN process due to the removal of the deposit layer caused by the occurrence of sputtering on the surface of the steel and the increase in the plasma formation area caused by the plasma formation on the surfaces of the screen and the steel. However, even with the S-DCPN process, it takes about 50 hours for the desired surface characteristics to be obtained in the case of low-temperature nitriding.
[0026] Generally, the screens in the ASPN and S-DCPN processes are made of steel. In contrast, the inventors of the present invention performed the ASPN process on low-carbon steel S15C using a Ni (nickel) screen and a steel screen. Similarly, the S-DCPN process was performed on low-carbon steel S15C using a Ni screen and a steel screen. As a result, the following conclusion was obtained (Non-Patent Document 2).
[0027] (1) In both the ASPN and S-DCPN treatments, the amount of nitrogen diffusion was greater when a Ni screen was used than when a steel screen was used. Furthermore, when a Ni screen was used, the amount of nitrogen diffusion was greater when the S-DCPN treatment was used than when the ASPN treatment was used.
[0028] (2) In the ASPN treatment, when a Ni screen was used, a deposit layer containing a large amount of Ni from the screen was formed on the surface of the sample, and a compound layer was formed underneath it. In addition, the surface hardness was lower than when a steel screen was used, but the sample showed high corrosion resistance.
[0029] (3) When a Ni screen was used in the S-DCPN treatment, two compound layers with different hardness were formed, and about 20 at% Ni was detected in the hard compound layer. In addition, compared to when a steel screen was used, the surface hardness was higher, but the corrosion resistance was lower.
[0030] [Embodiment] Therefore, the inventors of the present application considered performing S-DCPN treatment using a Ni screen on a stainless steel material, and devised the following embodiment.
[0031] Fig. 1 is a cross-sectional view showing an overview of a plasma nitriding apparatus according to this embodiment. The plasma nitriding apparatus 1 of this embodiment performs S-DCPN treatment on a stainless steel material 2. As shown in Fig. 1, the plasma nitriding apparatus 1 includes a gas supply unit 11, a main body unit 12, a pump unit 13, a power supply unit 14, and a temperature measurement unit 15.
[0032] (Gas supply section) The gas supply unit 11 mixes a plurality of gases including nitrogen gas (N2) at a predetermined ratio and supplies the mixed gas to the main body unit 12. In this embodiment, the gas supply unit 11 includes a nitrogen cylinder 21, a hydrogen cylinder 22, a flow meter 23, and a mixer 24.
[0033] The nitrogen cylinder 21 is a container that contains compressed high-pressure nitrogen gas (N2), and the hydrogen cylinder 22 is a container that contains compressed high-pressure hydrogen gas (H2). The nitrogen gas from the nitrogen cylinder 21 and the hydrogen gas from the hydrogen cylinder 22 are supplied to a mixer 24.
[0034] The flow meter 23 measures the flow rate of the nitrogen gas supplied from the nitrogen cylinder 21 to the mixer 24 and the flow rate of the hydrogen gas supplied from the hydrogen cylinder 22 to the mixer 24 .
[0035] The mixer 24 mixes the nitrogen gas and the hydrogen gas at a predetermined ratio (for example, N2:H2=20:80 to 80:20) The mixer 24 supplies the mixed gas to the main body 12.
[0036] (Main body) The main body 12 includes a vacuum reactor 31. The vacuum reactor 31 is a metal container for causing various reactions, such as chemical reactions, to a workpiece such as a stainless steel material 2 under vacuum conditions.
[0037] An air inlet 31a through which the mixed gas from the gas supply unit 11 flows in is provided at a suitable position on the inner upper surface of the vacuum reactor 31. An exhaust port 31b for exhausting the air inside is provided at a suitable position on the inner lower surface of the vacuum reactor 31. An opening 31c is formed at a suitable position on the inner side surface of the vacuum reactor 31, and a glass window 32 is provided in the opening 31c.
[0038] A conductive base 34 is provided on the bottom surface of the vacuum reactor 31 via an insulating member 33. A nickel plate 35 (hereinafter referred to as "Ni plate 35") is provided on the entire upper surface of the base 34. This is to suppress the influence of metal nitrides originating from the base 34 on the stainless steel material 2. The stainless steel material 2 is provided in the center of the Ni plate 35 via a conductive adjustment table 36. This allows the stainless steel material 2 to be placed in an optimal position for the S-DCPN treatment.
[0039] A nickel screen 37 (hereinafter referred to as "Ni screen 37") is provided on the edge of the Ni plate 35. The Ni screen 37 is a mesh member provided so as to cover the stainless steel material 2. Therefore, the mixed gas can pass through the Ni screen 37 and reach the stainless steel material 2.
[0040] An anode member 38 is disposed on the inner wall of the vacuum reactor 31 via an insulating member (not shown). The anode member 38 is a conductive member that functions as an anode for generating an arc discharge in the vacuum reactor 31. The base 34, the Ni plate 35, the adjustment table 36, the Ni screen 37, and the stainless steel material 2 function as a cathode for generating the arc discharge. The vacuum reactor 31 and the anode member 38 may be integrated together.
[0041] Furthermore, a thermocouple 39 is provided at an appropriate position within the vacuum reactor 31. The thermocouple 39 measures the temperature within the vacuum reactor 31.
[0042] (Pump section) The pump section 13 includes a vacuum pump 41 and a vacuum gauge 42. The vacuum pump 41 exhausts the air in the vacuum reactor 31 of the main body section 12 through the exhaust port 31b. Examples of the vacuum pump 41 include a rotary pump, a diffusion pump, and a turbo pump. The vacuum gauge 42 measures the degree of vacuum in the vacuum reactor 31.
[0043] (others) The power supply unit 14 includes a DC power supply 43. An anode of the DC power supply 43 is electrically connected to the anode member 38 in the vacuum reactor 31, and a cathode of the DC power supply 43 is electrically connected to the base 34. The DC power supply 43 is configured to apply a predetermined voltage between the anode member 38 in the vacuum reactor 31 and the base 34. The voltage applied by the DC power supply 43 is measured by a voltmeter (not shown).
[0044] The temperature measurement unit 15 includes a radiation thermometer 44 and a support base 45 that supports the radiation thermometer 44. The radiation thermometer 44 detects the intensity of electromagnetic waves emitted from the stainless steel material 2 through the glass window 32 to measure the temperature of the stainless steel material 2. An example of the radiation thermometer 44 is an infrared thermometer. The radiation thermometer 44 may be a thermograph that shows the above-mentioned temperature distribution as a two-dimensional image.
[0045] In the plasma nitriding apparatus 1 having the above configuration, the amount of nitrogen diffusion can be improved and the expansion phase film can be formed quickly by using the Ni screen 37, compared to the case where a conventional screen made of steel material is used. As a result, the amount of nitrogen used in the low-temperature nitriding process can be reduced, and the process time can be shortened.
[0046] (S-DCPN processing) Next, the S-DCPN process (plasma nitriding process) in the plasma nitriding apparatus 1 configured as above will be described. First, the stainless steel material 2 is placed at an appropriate position in the vacuum reactor 31 using the base 34 and the adjustment table 36, and the radiation thermometer 44 is focused on the stainless steel material 2. Next, the vacuum reactor 31 is depressurized using the vacuum pump 41, and then the mixed gas is introduced into the vacuum reactor 31 and exhausted, thereby maintaining the inside of the vacuum reactor 31 at a predetermined pressure (for example, 100 Pa to 1000 Pa, preferably 100 Pa to 200 Pa).
[0047] Next, a voltage is applied between the anode member 38 and the base 34, the Ni plate 35, the adjustment table 36, the Ni screen 37, and the stainless steel material 2 using the DC power supply 43, and a DC current is gradually passed to generate a glow discharge. As a result, plasma is generated in the vicinity of the stainless steel material 2 and the Ni screen 37 (the region indicated by the dashed line in FIG. 1).
[0048] Nitrogen ions in the plasma near the stainless steel material 2 cause sputtering on the surface of the stainless steel material 2. This removes unnecessary deposition layers on the surface of the stainless steel material 2. The sputtering also produces metal nitrides (MN) with a high nitrogen concentration, which are deposited on the stainless steel material 2. The nitrogen released in the process of decomposing the metal nitrides with a high nitrogen concentration into metal and nitrogen diffuses into the interior of the stainless steel material 2, and nitridation progresses.
[0049] In addition, nitrogen ions in the plasma near the Ni screen 37 cause sputtering on the surface of the Ni screen 37, producing nickel nitride (NiN) with a high nitrogen concentration. The nickel nitride is deposited on the stainless steel material 2 by the gas flow in the vacuum reactor 31. The high nitrogen concentration nickel nitride deposited on the stainless steel material 2 is decomposed into nickel and nitrogen, and the released nitrogen diffuses into the stainless steel material 2, progressing the nitridation.
[0050] The nitriding process is carried out for a predetermined processing time (e.g., 3 hours to 20 hours) at a predetermined temperature (processing temperature) of the stainless steel material 2 (e.g., 620K to 700K) lower than the normal temperature (723K). Thereafter, the application of the voltage is terminated, and the mixed gas is allowed to flow into the vacuum reactor 31 to cool the stainless steel material 2 until its temperature drops to near room temperature. Next, air is introduced into the vacuum reactor 31, and the stainless steel material 2 is removed.
[0051] (Additional Notes) In this embodiment, the Ni screen 37 is in a mesh shape and is provided so as to cover the stainless steel material 2, but is not limited to this. The Ni screen 37 can be in any shape, such as a cylindrical shape, as long as nickel nitride with a high nitrogen concentration can reach the stainless steel material 2. In this embodiment, the material of the Ni screen 37 is nickel (pure nickel), but is not limited to this. For example, it may be a nickel-based alloy containing nickel as a main component (e.g., 40% or more) so that sputtering occurs on the surface of the screen to generate nickel nitride with a high nitrogen concentration. EXAMPLES
[0052] An embodiment of the S-DCPN process using the plasma nitridation apparatus 1 having the above configuration will be described below.
[0053] (Stainless steel) In this embodiment, as the stainless steel material 2, austenitic stainless steel SUS304 steel material (SUS304 steel material), ferritic stainless steel SUS430 steel material (SUS430 steel material), and duplex stainless steel SUS329J4L steel material (SUS329J4L steel material) were used.
[0054] Figure 2 is a diagram showing the chemical compositions of the above three materials in tabular form. For each of the above three materials, a bar was prepared, and the bar was processed into a disk shape with a diameter of 25 mm and a thickness of 5 mm. The upper surface was wet polished with #220 to #2000 and finally mirror-finished by buffing with alumina powder with a particle size of 1 μm.
[0055] (S-DCPN processing) A direct current plasma nitriding device (model: JIN-1S) manufactured by Nippon Electric Industry Co., Ltd. was used, and the Ni plate 35 of this embodiment, an adjustment table 36, a Ni screen 37, and a stainless steel material 2 were provided in the direct current plasma nitriding device. The Ni screen 37 had a diameter of 100 mm and a height of 56 mm, and was made of Ni mesh material (0.15 mm diameter wire, 50 mesh, aperture ratio 49.7%). A SUS430 round bar member was installed as the adjustment table 36 so that the distance between the upper surface of the stainless steel material 2 and the Ni screen 37 was 15 mm.
[0056] Then, in the vacuum reactor 31, the pressure was evacuated to 10 Pa or less, and then a mixed gas of 75% N2 + 25% H2 was introduced, and the pressure in the mixed gas atmosphere was kept constant at 100 Pa. Then, the S-DCPN process was performed at a process temperature of 673 K for a process time of 300 minutes.
[0057] (Comparative Example) The comparative example was subjected to the S-DCPN treatment in the same manner as the above-mentioned example, except that the Ni plate 35 was removed and a screen made of cold-rolled steel plate (Steel Plate Cold Commercial, SPCC) (hereinafter referred to as "SPCC screen") was provided instead of the Ni screen 37. The SPCC screen had the same dimensions as the Ni screen 37, and was made of expanded metal (LW=4.0mm, SW=8.0mm, T=0.5mm, W=0.8mm, aperture ratio 66.3%).
[0058] (result) The stainless steel materials used in the above examples and comparative examples were evaluated as follows.
[0059] (XRD analysis) In order to identify the surface of the S-DCPN treated stainless steel material, an X-ray diffraction (XRD) test was performed using an X-ray diffraction measurement tester (model: RINT-2200) manufactured by Rigaku Corporation. The X-ray source used was Cu-Kα radiation (wavelength λ = 0.15405 nm), and the measurement was performed at a tube voltage of 40 kV and a tube current of 300 mA.
[0060] Figure 3 is a graph showing the results of the above-mentioned XRD test for S-DCPN treated SUS304 steel, SUS430 steel, and SUS329J4L steel. The horizontal axis of each graph is the diffraction angle 2θ, and the vertical axis is the intensity (arbitrary unit). Each graph also shows an example using a Ni screen 37, a comparative example using a SPCC screen, and an untreated example in which the above-mentioned S-DCPN treatment was not performed.
[0061] From the graph in the upper part of FIG. 3, in both the examples and comparative examples of the SUS304 steel material, the diffraction lines of the γ phase of the substrate and the broadened diffraction lines of the expanded austenite phase (S phase) were confirmed, in which the diffraction lines of the γ phase were shifted to the low angle side. Also, from the graph in the middle part of FIG. 3, in both the examples and comparative examples of the SUS430 steel material, the diffraction lines of the expanded ferrite phase (Sα phase) were confirmed, in which the diffraction lines of the α phase of the substrate were shifted to the low angle side. Although not shown in the graph above due to low detection intensity, the diffraction lines of CrN were detected at a diffraction angle of about 63.3°. Also, from the graph in the lower part of FIG. 3, in both the examples and comparative examples of the SUS329J4L material, the diffraction lines of the γ phase, α phase, and S phase of the substrate were confirmed, but the diffraction lines of the Sα phase were not confirmed.
[0062] The above shift and broadening are caused by the supersaturation of nitrogen (N) in the crystal lattice of the gamma and alpha phases. At this time, compressive residual stress is introduced, stacking fault density is increased, and large elastic strain occurs in the crystal lattice, resulting in improved mechanical properties such as wear resistance and surface hardness of the stainless steel material.
[0063] Figure 4 is a table showing the results of calculating the expansion rate of the lattice constant using the diffraction angle of the expansion phase of each stainless steel material obtained from the graph in Figure 3. Referring to Figure 4, it can be seen that in all of the stainless steel materials treated with S-DCPN, the expansion rate is larger in the example using Ni screen 37 than in the comparative example using SPCC screen at the same lattice plane, and more nitrogen (N) is dissolved in the crystal lattice.
[0064] Also, referring to FIG. 4, it can be seen that the expansion rate of the S(200) plane is greater than that of the S(111) plane, and the crystal lattice expands anisotropically. This is because, in the fcc structure of γ-Fe, <111> The direction is <200> This is believed to be due to the fact that the SiO2 direction has a higher elastic modulus and a lower diffusion rate of N than the SiO2 direction.
[0065] (GD-OES analysis) For the purpose of elemental analysis from the surface to the depth direction of S-DCPN-treated stainless steel materials, glow discharge optical emission spectrometry (GD-OES) was performed using a Marcus-type high-frequency glow discharge optical emission surface analyzer (model: GD-Profiler2) manufactured by HORIBA, Ltd.
[0066] Fig. 5 is a graph showing the nitrogen (N) element profiles obtained by the above-mentioned GD-OES for S-DCPN-treated SUS304 steel, SUS430 steel, and SUS329J4L steel. The horizontal axis of each graph is the distance d (μm) from the surface, and the vertical axis is the nitrogen (N) concentration (at%). In each graph, the working example using the Ni screen 37 is shown by a solid line, and the comparative example using the SPCC screen is shown by a dashed line.
[0067] 5, it can be seen that the amount of nitrogen diffused into the stainless steel material is greater in the above-mentioned Examples than in the above-mentioned Comparative Examples for all of the SUS304, SUS430, and SUS329J4L steel materials. This result is similar to the result of Non-Patent Document 2, which conducted a similar experiment on low carbon steel S15C. This is thought to be because the nickel nitride derived from the Ni screen 37 is less stable than the iron nitride derived from the SPCC screen, and more of it is decomposed on the surface of the stainless steel material 2, and a lot of nitrogen (N) is diffused into the inside of the stainless steel material 2.
[0068] In addition, in Non-Patent Document 2, the amount of nitrogen diffused was smaller in the case of using a Ni screen than in the case of using an SPCC screen at a position of 0 to 1 μm from the surface. In contrast, referring to the graph in FIG. 5, the amount of nitrogen diffused was larger in the example using a Ni screen than in the comparative example using an SPCC screen, even at a position of 0 to 1 μm from the surface. From this, the present example in which the S-DCPN treatment is performed on a stainless steel material using a Ni screen is more effective in forming an extended phase film more quickly than in the case of Non-Patent Document 2 in which the S-DCPN treatment is performed on a low carbon steel material using a Ni screen.
[0069] Furthermore, comparing the upper and lower graphs in Figure 5 with the middle graph in Figure 5, it can be seen that in the case of S-DCPN-treated SUS304 steel and SUS329J4L steel, the N concentration is high in the region 3 to 4 μm from the surface, but the diffusion depth is small. On the other hand, in the case of S-DCPN-treated SUS430 steel, it can be seen that the N concentration is low in the region 3 to 4 μm from the surface, but the diffusion depth is large. This is thought to be because the solid solubility of nitrogen (N) atoms is smaller in α-Fe than in γ-Fe, and the diffusion rate of nitrogen (N) atoms is faster in α-Fe than in γ-Fe.
[0070] (EPMA analysis) In order to analyze the cross-section and surface structure of the S-DCPN-treated stainless steel, an Electron Probe Micro Analyzer (EPMA) was used to analyze the cross-section and surface structure using an Electron Probe Micro Analyzer (Model: JXA-8230) manufactured by JEOL Ltd. When observing the cross-section structure, electrolytic corrosion was performed using 5 mass% oxalic acid as an etching solution. At this time, the S-DCPN-treated SUS304 steel was subjected to 15 seconds at 5V, the S-DCPN-treated SUS430 steel was subjected to 5 seconds at 3V, and the S-DCPN-treated SUS329J4L steel was subjected to 10 seconds at 5V.
[0071] Fig. 6 is a photograph showing the results of observing the cross-sectional structure of the example and comparative example of SUS304 steel material by EPMA. The left side of Fig. 6 is a photograph of the example using Ni screen 37, and the right side of Fig. 6 is a photograph of the comparative example using SPCC screen.
[0072] Referring to Fig. 6, a nitride layer was observed on the surface of both the example and the comparative example of the SUS304 steel material. This nitride layer is considered to be composed of S phase, based on the graph in the upper part of Fig. 3. The thickness of the nitride layer (position of the arrow in Fig. 6) was 3.6 ± 0.1 µm in the example using the Ni screen 37, and 2.1 ± 0.1 µm in the comparative example using the SPCC screen. Therefore, the nitride layer (S phase) formed in the example using the Ni screen was about 1.7 times thicker than that formed in the comparative example using the SPCC screen.
[0073] Fig. 7 is a photograph showing the results of observing the cross-sectional structure of the example and comparative example of SUS430 steel by EPMA. The inset in Fig. 7 is a photograph showing an enlarged view of the surface portion of the example and comparative example of SUS430 steel. The left side of Fig. 7 is a photograph of the example using Ni screen 37, and the right side of Fig. 7 is a photograph of the comparative example using SPCC screen.
[0074] Referring to FIG. 7, no clear nitride layer was observed on the surface in either the example or the comparative example of the SUS430 steel material. This indicates that there is no significant difference in the microstructure between the Sα phase and the α phase of the base material. In addition, needle-shaped iron nitride precipitates were observed in either the example or the comparative example of the SUS430 steel material. This result is thought to be due to the formation of the Sα phase, which was not identified in the middle graph of FIG. 3.
[0075] In addition, in the inset of Fig. 7, strongly etched regions were observed on the surface of the SUS430 steel in both the example and comparative example of the SUS430 steel. As described above, although the diffraction line intensity was low, CrN was identified, and therefore the above-mentioned regions are considered to be due to a decrease in corrosion resistance caused by CrN precipitation.
[0076] Fig. 8 is a photograph showing the results of observing the cross-sectional structure of an example and a comparative example of SUS329J4L steel material by EPMA. The left side of Fig. 8 is a photograph of an example using a Ni screen 37, and the right side of Fig. 8 is a photograph of a comparative example using a SPCC screen. The upper part of Fig. 8 is a photograph at a higher magnification than the lower part of Fig. 8. Regarding the α-phase and γ-phase in Fig. 8, the phase in which Cr and Mo are concentrated was determined to be the α-phase from the results of the EPMA analysis, and the phase in which Ni is concentrated was determined to be the γ-phase.
[0077] Referring to Fig. 8, in both the examples and comparative examples of SUS329J4L steel, a nitride layer was observed on the surface, regardless of the α-phase and γ-phase. Therefore, elemental analysis was performed by EPMA at the center of the cross section of the nitride layer for each of the α-phase and γ-phase. As a result, in the example using the Ni screen 37, the nitrogen (N) concentration was 23.2 at% in the α-phase and 23.7 at% in the γ-phase. On the other hand, in the comparative example using the SPCC screen, the nitrogen (N) concentration was 23.3 at% in the α-phase and 22.9 at% in the γ-phase.
[0078] That is, the nitrogen (N) concentration detected in the center of the nitrided layer was similar in the examples and comparative examples, and was similar in the α phase and the γ phase. From this and the fact that the Sα phase was not identified but only the S phase was identified in the lower graph of Figure 3, it is believed that the S phase was formed not only in the γ phase but also in the α phase. In other words, it is possible that the diffusion of N, a strong γ-stabilizing element, into the α phase caused a phase transformation as shown in the following formula (1), ultimately resulting in the formation of the S phase.
[0079] α→(Sα,γ)→S ···(1).
[0080] In addition, referring to Fig. 8, in the comparative example, needle-like structures were observed in both the α-phase and γ-phase nitrided layers. On the other hand, in the example, needle-like structures were not observed in the γ-phase nitrided layer, but were observed in the α-phase nitrided layer. Further investigation is required to determine the cause of this.
[0081] In the embodiment using the Ni screen 37, the thickness of the nitride layer (position of the arrow in FIG. 8) was 3.7±0.1 μm in the α phase and 3.4±0.3 μm in the γ phase. On the other hand, in the comparative example using the SPCC screen, the thickness of the nitride layer was 2.9±0.2 μm in the α phase and 2.5±0.2 μm in the γ phase. Therefore, the nitride layer (S phase) formed in the embodiment using the Ni screen was about 1.3 times thicker than that formed in the comparative example using the SPCC screen. In both the embodiment and the comparative example, the nitride layer (S phase) formed in the α phase was thicker than the nitride layer (S phase) formed in the γ phase. This is thought to be because the diffusion coefficient of nitrogen (N) is larger in the α phase than in the γ phase, and nitrogen (N) atoms diffuse preferentially into the α phase.
[0082] Furthermore, referring to the photograph in the lower part of FIG. 8, in the comparative example in which the SPCC screen was used, locally thin regions of the S phase were observed without distinction between the α phase and the γ phase, whereas in the example in which the Ni screen was used, the above-mentioned thin regions were not observed.
[0083] (Surface hardness test) In order to investigate the surface hardness of the S-DCPN treated stainless steel, a surface hardness test was carried out using a Matsuzawa Co., Ltd. micro Vickers hardness tester (model: PMT-X7A).
[0084] Fig. 9 is a graph showing the results of the above surface hardness test on S-DCPN treated SUS304 steel, SUS430 steel, and SUS329J4L steel. Referring to the graph in Fig. 9, it can be seen that the surface hardness of the stainless steel materials of the examples and comparative examples is improved compared to the untreated stainless steel materials in all of the SUS304 steel, SUS430 steel, and SUS329J4L steel. This improvement in surface hardness is thought to be due to the formation of S phase in the SUS304 steel and SUS329J4L steel, and due to Sα phase and precipitation strengthening (iron nitrides, CrN, etc.) in the SUS430 steel.
[0085] It can also be seen that the examples using the Ni screen 37 have a higher surface hardness than the comparative examples using the SPCC screen for all of the SUS304, SUS430, and SUS329J4L steels. In the case of the SUS329J4L steel, the examples using the Ni screen show the same surface hardness regardless of the α-phase and γ-phase, while the comparative examples using the SPCC screen show two regions with different surface hardness. For this reason, the surface structure after the Vickers hardness test was observed and analyzed by EPMA.
[0086] Fig. 10 is a photograph showing the results of the surface texture observation. Fig. 11 is a table showing the results of the elemental analysis. The left side of Fig. 10 is a photograph of an example using a Ni screen 37, and the right side of Fig. 10 is a photograph of a comparative example using a SPCC screen.
[0087] 10 and 11, in the example using the Ni screen 37 in the SUS329J4L steel material, the nitrogen (N) concentration was approximately the same in the α phase (α1) and the γ phase (γ1). In contrast, in the comparative example using the SPCC screen, the nitrogen (N) concentration in the area with high surface hardness (α2, γ2) was approximately 30 at%, while the nitrogen (N) concentration in the area with low surface hardness (α3, γ3) was approximately 20 at%. From this, it is considered that the formation of areas with different surface hardness is due to the uneven distribution of the nitrogen (N) concentration.
[0088] (pitting corrosion resistance) A polarization curve was measured for the stainless steel material treated with S-DCPN in order to investigate the pitting corrosion resistance against salt water. Specifically, a lead wire made of SUS304 was spot welded to the stainless steel material 2, and the stainless steel material 2 was covered with Teflon (registered trademark) tape with a hole of 6 mm in diameter to limit the liquid contact area. In addition, a 3.5 mass% NaCl aqueous solution was used as the test solution, Ag / AgCl was used as the reference electrode, and Pt was used as the counter electrode. In addition, the voltage was controlled from -1.0 V to +1.5 V using a potentiostat (model: HA-501G) manufactured by Hokuto Denko Corporation, and the current density was recorded using a data logger (model: GL200A-UM801) manufactured by Graphtec Corporation. Finally, the corroded surface formed on the stainless steel material 2 was observed using an optical microscope (model: BX-60M) manufactured by Olympus Corporation.
[0089] Fig. 12 is a graph showing the results of polarization tests on S-DCPN treated SUS304 steel, SUS430 steel, and SUS329J4L steel. The vertical axis of the graph in Fig. 12 is the pitting potential, which is expressed as a function of current density i=1 Am -2 is the potential at
[0090] Figure 13 is a photograph showing the corroded surface after the polarization test. Note that SUS329J4L steel has high pitting corrosion resistance, and corrosion marks were only observed in the gap between the SUS329J4L steel and the Teflon tape. For this reason, the gap is shown in Figure 13 for the SUS329J4L steel.
[0091] There are several theories proposed as to why the formation of the S phase and Sα phase improves the pitting corrosion resistance of stainless steels, but the most widely supported proposal is that the solute N suppresses the drop in pH in the pits. - The pits are locally destroyed by the ion beam, and the reaction of the following formula (2) occurs due to the dissolved nitrogen in the pits, resulting in localized low pH and high Cl, which are the cause of active dissolution. - It inhibits the formation of an environment that inhibits pit growth and promotes repassivation.
[0092] [N]+4H + +3e - →NH4 + (2).
[0093] 12 and 13, it can be seen that the pitting corrosion resistance was improved in both the Example and Comparative Example of SUS304 steel because the pitting corrosion potential was higher and the corroded area was smaller than that of untreated SUS304 steel. Also, the Example using the Ni screen had a higher pitting corrosion potential and better pitting corrosion resistance than the Comparative Example using the SPCC screen.
[0094] In addition, in both the examples and comparative examples of SUS430 steel, the pitting potential was lower and the corroded area was larger than that of untreated SUS430 steel, so it can be understood that the pitting resistance was reduced. This is thought to be due to a decrease in solute Cr due to the precipitation of CrN, as suggested by the graph in the middle of Figure 3 and the photograph in Figure 7. It can also be understood that the examples using the Ni screen had a lower pitting potential and a greater decrease in pitting resistance than the comparative example using the SPCC screen.
[0095] In addition, in both the examples and comparative examples of SUS329J4L steel, the pitting potential was higher and the area of crevice corrosion was smaller than that of untreated SUS329J4L steel, so it can be understood that the pitting corrosion resistance was improved. In addition, the example using the Ni screen had a higher pitting potential than the comparative example using the SPCC screen, but the difference was small and was about the same. This is because, as can be seen by comparing the pitting potentials of each untreated steel in Figure 12, SUS329J4L steel is inherently superior in pitting corrosion resistance, unlike SUS304 steel and SUS430 steel. In addition, elemental analysis was performed by EPMA to further analyze the crevice corrosion part of the SUS329J4L steel.
[0096] Fig. 14 is a photograph showing the results of elemental analysis of the crevice corrosion part. In Fig. 14, the upper part shows an example using a Ni screen, and the lower part shows untreated SUS329J4L steel. Although not shown in Fig. 14, the crevice corrosion part of the comparative example using an SPCC screen also showed a similar morphology to the crevice corrosion part of the example using a Ni screen.
[0097] Referring to Figure 14, in the untreated SUS329J4L steel material, corrosion marks were observed over a wide area, and the α phase, in which Mo was more abundant, was corroded more strongly than the γ phase, in which Ni was more abundant, and the corrosion progress differed depending on the phase. On the other hand, in the examples and comparative examples, the area of the corrosion marks was narrower than that of the untreated SUS329J4L steel material, but the corrosion marks were deeper, and no variation in the corrosion progress was observed depending on the phase. This is thought to be because, as shown in the results of elemental analysis by EPMA in Figure 11, the S phase, which contains the same nitrogen (N) concentration, was formed in the α phase and the γ phase, making the pitting corrosion resistance of the surface uniform.
[0098] (Consideration) (Effect of Ni screen on low-temperature plasma nitriding of austenitic stainless steel using a screen) In the case of austenitic stainless steel (SUS304 steel), as shown in the GD-OES measurement results in the upper part of Figure 5, the amount of nitrogen diffusion was improved by using the Ni screen 37, and it is believed that this resulted in the formation of a thicker S phase in which more nitrogen (N) was dissolved in the crystal lattice, as shown in the upper part of Figure 3, the XRD test results in Figure 4, and the cross-sectional structure observation results in Figure 6. As a result, it is believed that the surface hardness and pitting corrosion resistance were further improved, as shown in the results of the surface hardness test in Figure 9 and the pitting corrosion tests in Figures 12 and 13.
[0099] (Effect of Ni screen on low-temperature plasma nitriding of ferritic stainless steel using a screen) In the case of ferritic stainless steel (SUS430 steel), as shown in the results of GD-OES measurement in the middle of Figure 5, the amount of nitrogen diffusion was improved by using Ni screen 37, and therefore, as shown in the middle of Figure 3 and the XRD test in Figure 4, Sα phase in which more nitrogen (N) is dissolved in the crystal lattice was formed, nitride precipitation was promoted, and surface hardness was improved. However, CrN precipitation was also promoted, and therefore pitting corrosion resistance was further reduced, as shown in the results of pitting corrosion tests in Figures 12 and 13. No tendency for these nitrides to precipitate was observed in SUS304 steel and SUS329J4L steel.
[0100] This is believed to be because the solid solubility limit of nitrogen (N) in the Sα phase is smaller than that in the S phase. This is expected because the solid solubility limit of nitrogen (N) is smaller in α-Fe than in γ-Fe, and the lattice constant expansion rate is smaller in the Sα phase than in the S phase, as shown in the XRD test results in Figure 4. In the examples, it is believed that nitrogen (N) diffused beyond the solid solubility limit of the Sα phase, causing the precipitation of CrN and iron nitrides.
[0101] (Effect of Ni screen on low-temperature plasma nitriding of duplex stainless steel) In the case of duplex stainless steel (SUS329J4L steel), as shown in the GD-OES measurement results in the bottom row of Figure 5, the amount of nitrogen diffusion was improved by using a Ni screen 37, which is believed to have resulted in the formation of a thicker S phase with more nitrogen (N) dissolved in the crystal lattice, as shown in the results of the XRD test in the middle row of Figure 3 and Figure 4, and the cross-sectional structure observation in the top row of Figure 8. As a result, it is believed that the surface hardness and pitting corrosion resistance were further improved, as shown in the surface hardness test results in Figure 9 and the pitting corrosion test results in Figures 12 and 13.
[0102] In addition, in the sample using the SPCC screen, the cross-sectional structure observation results in the lower part of FIG. 8 confirmed the formation of a thin S phase locally, and the surface hardness test results in FIG. 9 to FIG. 11 confirmed phases with different hardness and nitrogen (N) concentration on the surface of the sample, suggesting an uneven distribution of the nitrogen (N) concentration. This is thought to be due to the fact that the diffusibility of nitrogen (N) differs depending on the lattice plane, and that iron nitride derived from the SPCC screen is more difficult to decompose than nickel nitride derived from the Ni screen. In addition, nickel nitride is more easily decomposed on the sample surface than iron nitride, and it is thought that a lot of nitrogen (N) diffuses into the sample, so that the example using the Ni screen 37 has a larger amount of nitrogen diffusion than the comparative example using the SPCC screen, as shown in the GD-OES measurement results in the lower part of FIG. 5.
[0103] From these findings, it is believed that on the surface of duplex stainless steel, iron nitrides were easily decomposed on lattice planes with large nitrogen (N) diffusivity and difficult to decompose on small lattice planes, which resulted in different amounts of nitrogen diffusion depending on the lattice plane, forming a thin S phase and phases with different surface hardness and nitrogen (N) concentrations. On the other hand, the nitrogen (N) concentration was uniformly distributed in the sample using Ni screen 37 because nickel nitrides were easily decomposed, and therefore easily decomposed on both lattice planes with small and large nitrogen (N) diffusivity on the surface of duplex stainless steel, resulting in the amount of nitrogen diffusion being about the same on both lattice planes.
[0104] (Conclusion) In this example, in order to thicken the S-phase and Sα-phase in low-temperature plasma nitriding using a screen, an austenitic stainless steel material (SUS304 steel material), a ferritic stainless steel material (SUS430 steel material), and a duplex stainless steel material (SUS329J4L steel material) were subjected to S-DCPN treatment using Ni screen 37 and SPCC screen, and the results were compared. As a result, the following conclusions were obtained.
[0105] (1) In the S-DCPN treatment of SUS304 steel, when Ni screen 37 was used, the amount of nitrogen diffusion was improved and the S phase became thicker than when SPCC screen was used. As a result, the surface hardness and pitting corrosion resistance were improved.
[0106] (2) In the S-DCPN treatment of SUS430 steel, when Ni screen 37 was used, the amount of nitrogen diffusion was improved compared to when SPCC screen was used, but the thickness of the Sα phase could not be measured. In addition, the surface hardness was improved, but the pitting corrosion resistance was lower than that of untreated SUS430 steel with both Ni screen 37 and SPCC screen due to CrN precipitation, and was even lower when Ni screen was used.
[0107] (3) In the S-DCPN treatment of SUS329J4L steel, when Ni screen 37 was used, the amount of nitrogen diffusion was improved compared to when SPCC screen was used, resulting in a thicker S phase. As a result, the surface hardness and pitting corrosion resistance were improved.
[0108] (4) In low-temperature plasma nitriding using a screen, when a Ni screen37 is used, the amount of nitrogen diffusion is improved in austenitic stainless steel and duplex stainless steel compared to when a screen made of conventional steel material is used, resulting in a thicker S phase, and therefore improved surface hardness and pitting corrosion resistance. On the other hand, in ferritic stainless steel, the amount of nitrogen diffusion and surface hardness are improved, but attention must be paid to the associated decrease in pitting corrosion resistance due to CrN precipitation.
[0109] (Nickel diffusion) Furthermore, the diffusion of nickel into the stainless steel material in the above-mentioned examples was evaluated using the above-mentioned GD-OES.
[0110] FIG. 15 is a graph showing the nickel (Ni) element profiles obtained by the above GD-OES for the S-DCPN-treated SUS304 steel, SUS430 steel, and SUS329J4L steel. The horizontal axis of each graph is the distance d (μm) from the surface, and the vertical axis is the nickel (Ni) concentration (at%). In each graph, the working example using the Ni screen 37 is shown by a solid line, and the comparative example using the SPCC screen is shown by a dashed line. Since the SPCC screen does not contain nickel, the difference between the graph of the working example and the graph of the comparative example is considered to be the concentration of nickel diffused into the stainless steel material 2 by the Ni screen 37.
[0111] 15, it can be seen that in all of the SUS304, SUS430, and SUS329J4L steel materials, nickel is diffused into the stainless steel material 2 by the Ni screen 37, although the amount is small compared to nitrogen. The diffusion of nickel into the stainless steel material makes it easier to form a passive film on the surface of the stainless steel material, and it is expected that the corrosion resistance will be improved.
[0112] It can also be seen that when the distance from the surface is 0.1 μm or less, the amount of nickel diffused into the stainless steel material 2 is greatest for the SUS430 steel material, greatest for the SUS329J4L steel material, and greatest for the SUS304 steel material.
[0113] (Additional Notes) In this example, the nitrogen diffusion amount and surface hardness were improved in all of the austenitic stainless steel, ferritic stainless steel, and duplex stainless steel. From this, it is believed that the nitrogen diffusion amount and surface hardness will also be improved in martensitic stainless steel, precipitation hardening stainless steel, and other stainless steel materials by performing the S-DCPN treatment similar to that in this example.
[0114] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. [Explanation of symbols]
[0115] 1. Plasma nitriding equipment 2. Stainless steel 11 Gas supply section 12 Main body 13 Pump section 14 Power supply section 15 Temperature measurement part 21 Nitrogen Cylinder 22 Hydrogen Cylinder 23 Flow meter 24 Mixer 31 Vacuum Reactor 31a Air supply port 31b Exhaust port 31c opening 32 Glass Window 33 Insulating materials 34 Foundation 35 Ni plate 36 Adjustment stand 37 Screen 38 Anode member 39 Thermocouple 41 Vacuum Pump 42 Vacuum gauge 43 DC power supply 44 Radiation thermometer 45 Support stand
Claims
1. A plasma nitriding apparatus for performing plasma nitriding treatment on steel material, A base for placing the steel material; A nickel plate provided on the upper surface of the base; A screen disposed near the steel material; a DC power source having a cathode electrically connected to the steel material, the base, the nickel plate, and the screen; The steel material is a stainless steel material, The plasma nitriding apparatus, wherein the screen is formed from nickel or a nickel-based alloy.
2. 2. The plasma nitriding apparatus according to claim 1, wherein the stainless steel material is an austenitic, ferritic or duplex stainless steel material.
3. 3. The plasma nitriding apparatus according to claim 2, wherein the stainless steel material is an austenitic or duplex stainless steel material.
4. A plasma nitriding method for subjecting a steel material to a plasma nitriding treatment, comprising the steps of: The method includes a step of performing plasma nitriding treatment using the steel material, a base for placing the steel material, a nickel plate provided on an upper surface of the base, and a screen placed near the steel material as cathodes, The steel material is a stainless steel material, The plasma nitriding method, wherein the screen is formed from nickel or a nickel-based alloy.
5. The plasma nitriding method according to claim 4, wherein the stainless steel material is an austenitic, ferritic or duplex stainless steel material.
6. The plasma nitriding method according to claim 5 , wherein the stainless steel material is an austenitic or duplex stainless steel material.
Citation Information
Patent Citations
Insulating type multifunctional ion chemical heat treatment device
CN101591763A
Production of nitrided stainless steel
JP2000073156A
Plasma processing method and deposition method
JP2005064017A
Nitriding method with the use of post plasma, and nitriding apparatus
JP2007191784A
Corrosion- and wear-resistant member and method for manufacturing the same
JP2011042862A